A fully rotational joint underactuated finger mechanism and its kinematics analysis. (1st September 2016) - Licheng, Wu; Yanxuan, Kong; Xiali, Li
The characteristic features of underactuated finger are compact structure, large grasping force, and simple operation. It has a wide application prospect in the fields of industrial robot, humanoid robot, human artificial limb, and space robot. A new type of fully rotating joint linkage-based underactuated mechanism is proposed, and a new method based on the law of minimum resistance is presented to realize the equivalent mechanism at different contact conditions of the finger and the kinematical analysis based on the equivalent mechanism. The kinematic equations and the limit moving position of the mechanism are derived using the proposed method. Finally, the numerical simulation is carried out by MATLAB program. The correctness and effectiveness of the proposed method are verified. The simulation results show that the proposed mechanism has a large grasp space and can achieve good grasp trajectory.